Mediasi Iklim Etis Pada Kepemimpinan Etis Dan Organizational Citizenship Behavior - Bastian, Adolf; ., Anto Arianto (CV. ITTC INDONESIA, 2024)
This study employs a quantitative method with a descriptive and explanatory survey approach. The research was conducted at the Kampar Regency Land Office, aiming to examine the role of ethical climate in mediating the influence of ethical leadership on organizational citizenship behavior. The population of this study consists of all employees of the Kampar Regency Land Office, totaling 144 people. Based on this population size, the sample size for this study is 103 people, as determined by the Krejcie and Morgan table (1970). The sampling method used in this research is Systematic Random Sampling. All respondents will provide primary data related to the variables, collected through a questionnaire using a 1-5 point Likert scale. All obtained data will be analyzed using Structural Equation Modeling (SEM) with the Smart PLS 3.0 analysis tool. The analysis results indicate that ethical leadership has a significant positive effect on organizational citizenship behavior, ethical leadership has a significant positive effect on ethical climate, ethical climate has a significant positive effect on organizational citizenship behavior, and ethical climate mediates the influence of ethical leadership on organizational citizenship behavior.